(untitled) (International Journal of Built Environment and Sustainability, 2025)
This study aims to evaluate urban landscape planning resources, to reveal traditional and modern landscape planning approaches in an integrated manner. In addition, it is aimed to determine the place and usage areas of landscape in urban planning in order to increase the impact of urban landscape planning and contribute to its development. In this context, to carry out descriptive network and cluster analyzes and bibliometric analyzes of studies conducted in the field of urban landscape planning in peer-reviewed journals (4250 articles) between 2000 and 2021, using the WOS database and R program, within the framework of various parameters. The study reveals the 21-year development process of urban landscape planning and the interest/study tendency towards the subject. Within the scope of the bibliometric analysis results obtained in the study, which provides an overview of the field of urban landscape planning, the contributions of the studies on the subject to the field are determined and it is aimed to be a reference and guide for similar studies to be done in the future. According to the findings, the subjects of landscape, managemenet, sustainability, land use, ecosystem services, climate change come to the fore in the studies carried out intensively in China, the USA and the United Kingdom. The most influential journals in the field can be listed as Landscape and Urban Planning, Sustainability and Land. Although there are bibliometric studies in the field of Landscape Architecture, this study presents the first bibliometric approach with an overview by considering all the sources in the temporal process and scanned in the articles in the field of urban landscape planning. By identifying key thematic trends, the study will contribute to guiding future research and to the development of sustainable, nature-based urban planning policies.